Legal Protection for Victims of Traffic Accidents Due to Against The Law - Rafi Hidayahtullah Pakaya; Tutiek Retnowati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The occurrence of a traffic accident is an act against the law that can result in harm to other people, violators can be sentenced in the form of payment of compensation either materially or immaterially to the victim and their heirs. According to Article 1365 of the Civil Code states "every act that violates the law, which results in harm to others. It is obligatory for people who because of their actions to publish losses, are obliged to compensate for these losses", further article 1366 of the Civil Code states that "everyone is required to be responsible not only for losses caused by his actions, but for losses caused by negligence or lack of caution.